Electroluminescent difunctional electrode fiber and application thereof in preparation of electroluminescent device

Through electrospinning technology, nanofiber layers are prepared on the surface of zinc wire and the electrolyte formula is controlled, which solves the integration problem between electroluminescent devices and energy storage equipment, realizes the dual application of flexible electroluminescence and energy storage functions, and improves the equipment stability and performance.

CN119145086AActive Publication Date: 2024-12-17ZHEJIANG SCI-TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411300813.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-17
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

In the wearable device, existing electroluminescent devices have problems such as large drivers and not flexible, making it difficult to integrate stably with textiles. Electroluminescence requires insulation between the two electrodes, which leads to the insulating ability of zinc ions, which affects energy storage performance.

Method used

The nanofiber layer is prepared on the surface of zinc wire by electrospinning technology, and zinc sulfide copper and PDMS are added. By controlling the use of electrolyte formulation and photoinitiator, the preparation of dual-function electrode fibers can not only suppress side reactions, but also in zinc. Ion transmission channels are provided in the ion battery to adapt to the insulation requirements of electroluminescence.

Benefits of technology

实现了纤维状锌离子电池和电致发光器件的集成,提供了优异的电化学性能和柔性储能设备,降低了制备成本和能耗,增强了器件的稳定性和可穿戴性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145086A_ABST
    Figure CN119145086A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode fiber, in particular to an electroluminescent difunctional electrode fiber and application thereof in preparation of an electroluminescent device, and belongs to the technical field of electroluminescent electronic devices. The invention relates to a difunctional electrode fiber, which is prepared by the following method: taking a zinc wire with the diameter of 0.3-2.0 mm as a core wire, and performing electrostatic spinning on the surface of the zinc wire by adopting a spinning solution to form a nanofiber layer, thereby obtaining the difunctional electrode fiber, the spinning solution comprises the following components in percentage by weight: 15-25% of thermoplastic polyurethane, 5-20% of copper zinc sulfide, 2-10% of PDMS (Polydimethylsiloxane) and the balance of a solvent consisting of N-N dimethylformamide and tetrahydrofuran. According to the invention, two functions are integrated on one electrode fiber, a fibrous zinc ion battery and a fibrous electroluminescent device can be easily prepared by changing the formula in the electrolyte, and meanwhile, a third fiber can be introduced into the fibrous zinc ion battery to endow the fibrous zinc ion battery with the electroluminescent capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrode fiber, in particular to an electroluminescent dual-function electrode fiber and application thereof in preparing an electroluminescent device, belonging to the technical field of electroluminescent electronic devices. Background Art

[0002] Flexible alternating current electroluminescence (ACEL) is attracting academic and commercial attention in emerging fields of flexible electronics such as wearable health monitoring systems, electronic skin, and electronic textiles. Traditional sandwich-structured electroluminescent devices are usually attached to textiles in a rough manner. Since planar electroluminescence can easily peel off from textiles, the underlying assembly must be planarized. In contrast, yarn-like electroluminescent devices can be flexibly integrated with traditional yarns to form textile displays, which are not only more stable and flexible, but can also adapt to more stringent external effects.

[0003] However, since electroluminescence requires the use of alternating current, all electroluminescent devices currently on the market need to be equipped with a DC-to-AC driver. Due to the low mechanical deformation of current energy storage batteries, the driver is usually large and not flexible, which limits the use of electroluminescent devices. Therefore, how to prepare wearable energy storage devices with excellent electrochemical properties and high deformation and flexibility is the most important challenge in this field. One-dimensional aqueous zinc-ion batteries have the advantages of safety and high mechanical properties and are considered to be one of the most promising devices in one-dimensional structural batteries. At the same time, zinc-ion batteries using gel electrolytes have a similar structure to fiber-shaped electroluminescent devices, making it possible to give two functions to one electrode.

[0004] The nanofibers prepared by electrospinning have high orientation, high porosity, and insulation. The electroluminescent materials, namely copper zinc sulfide and PDMS, are attached to the nanofiber layer by electrospinning, which can effectively inhibit the occurrence of side reactions in the zinc ion battery system, while improving the zinc ion transmission channel and effectively improving the electrochemical performance of the zinc ion battery. At the same time, the nanofiber layer can also be used as the light-emitting layer and dielectric layer in the electroluminescent device, and effectively emit light after connecting to the alternating current. However, due to the insulation between the two electrodes required for electroluminescence, ions cannot be transmitted between the two electrodes, and energy cannot be stored. Therefore, how to effectively control the device structure and selectively prepare zinc ion batteries and electroluminescent devices has become a major system problem of the current system. Summary of the invention

[0005] The purpose of the present invention is to provide a bifunctional electrode fiber. The preparation method of the bifunctional electrode fiber has the advantages of being simple and convenient, low cost, continuous preparation, and green and environmentally friendly. The electrode fiber can be used to prepare fibrous zinc-manganese batteries and fibrous electroluminescent devices.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A bifunctional electrode fiber is prepared by the following method:

[0008] A zinc wire with a diameter of 0.3-2.0 mm is used as a core wire, and a spinning solution is used to electrospin the surface of the zinc wire to form a nanofiber layer, thereby preparing a dual-functional electrode fiber;

[0009] The spinning solution contains 15-25% of thermoplastic polyurethane, 5-20% of zinc copper sulfide, 2-10% of PDMS, and the balance is a solvent composed of NN dimethylformamide and tetrahydrofuran, the mass ratio of NN dimethylformamide to tetrahydrofuran in the solvent is 100:0-50:50, and the molecular weight of the thermoplastic polyurethane is 10000-50000.

[0010] The fibers attached to the zinc wire surface are controlled by adjusting the winding device speed, the funnel collector rotation speed, the injector flow rate and the positive and negative voltages.

[0011] Preferably, the electrospinning parameters are set as follows: the angle between the needle tip and the collector is 60°, the distance between the needle tip and the collector is 8 cm, the injection pump propels the spinning solution at a speed of 1.2 mL / h, 12-17 KV DC high voltage electricity is used during the spinning process, the funnel-shaped collector rotates at a speed of 120-240 rpm, and the winding device speed is 0.06 m / min.

[0012] Preferably, the spinning solution contains, by weight percentage, 18-20% thermoplastic polyurethane, 18-20% zinc copper sulfide, 7-8% PDMS, and the balance is a solvent composed of NN dimethylformamide and tetrahydrofuran, wherein the mass ratio of NN dimethylformamide to tetrahydrofuran in the solvent is 50:50. The best formula of the spinning solution is: 18.5% thermoplastic polyurethane, 18.5% zinc copper sulfide, 7.5% PDMS, 27.7% NN dimethylformamide, and 27.7% tetrahydrofuran.

[0013] The invention of the present invention is mainly in the preparation of bifunctional electrode fibers. Secondly, the present invention can selectively construct batteries or electroluminescent devices by controlling the preparation of electrolytes. The difficulty lies in that electroluminescent devices require no ion transmission, while batteries require ion transmission. How to selectively control the passage of ions in the nanofiber layer is the focus of the present invention. Hydrophobic PDMS is added in the present invention, so the nanofiber membrane will not be wetted when the electroluminescent gel precursor is used to construct the gel, so there will be no ion transmission. After the photoinitiator is added to the electrolyte, since the photoinitiator is an amphiphilic substance, the photoinitiator will penetrate into the nanofiber layer. At this time, the luminescent powder zinc copper sulfide and PDMS added to the nanofiber can provide more zinc ion transmission sites, thereby improving the battery performance.

[0014] In order to make the positive and negative electrodes of the battery in different environments and improve the battery performance, the present invention adopts two electrolytes, a neutral electrolyte and a weakly acidic electrolyte, to prepare a fibrous aqueous zinc ion battery.

[0015] The present invention can easily control whether the nanofiber layer will be wetted by controlling the components in the electrolyte, so that single-functional electrode fibers can be selectively prepared. When a third fiber is introduced into the system, the device can be given a second function, providing a new idea for the integrated application of flexible electronics.

[0016] A fibrous aqueous zinc ion battery made using the bifunctional electrode fiber of the present invention, wherein the fibrous zinc ion battery is made by the following method:

[0017] S1 Preparation of electrolyte

[0018] Adding acrylamide and zinc sulfate heptahydrate to water in sequence and mixing them evenly, then adding NN methylenebisacrylamide and a photoinitiator in sequence and mixing them evenly to obtain a neutral electrolyte; the neutral electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 45-55% zinc sulfate heptahydrate, 0.05-0.5% NN methylenebisacrylamide, 0.05-0.5% photoinitiator, and the balance is water;

[0019] Add acrylamide, zinc sulfate heptahydrate and manganese sulfate to a weak acid solution with a pH value of 2-3 and mix well, then add NN methylenebisacrylamide and a photoinitiator in sequence, and mix well to obtain a weak acid electrolyte; the weak acid electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 40-50% zinc sulfate heptahydrate, 5-10% manganese sulfate, 0.05-0.5% NN methylenebisacrylamide, 0.05-0.5% photoinitiator, and the balance is a weak acid solution, and the pH value of the solution is 3-5;

[0020] Preparation of S2 fiber-shaped aqueous zinc-ion batteries

[0021] The bifunctional electrode fiber is used as the negative electrode and inserted into a polytetrafluoroethylene tubular mold, and the neutral electrolyte prepared by S1 is injected into the mold for photoinitiation to obtain a bifunctional electrode fiber / photoinitiator gel electrolyte yarn;

[0022] The bifunctional electrode fiber and the conductive carbon filament are used as positive electrode current collectors, two bifunctional electrode fiber / photoinitiator gel electrolyte yarns are inserted into a heat shrink tube in parallel, and the weak acid electrolyte prepared by S1 is injected into the heat shrink tube using a syringe, and light initiation is performed to obtain a yarn-shaped aqueous zinc ion battery without a positive electrode;

[0023] S3 Active Material Loading

[0024] The positive electrode-free yarn-shaped aqueous zinc-ion battery prepared with S2 was used as a device. The manganese ions in the electrolyte were oxidized into manganese oxides and deposited on the surface of the positive electrode current collector by chronoamperometry or constant voltage charging for several minutes under constant voltage conditions using an electrochemical workstation or a blue electric workstation. The yarn-shaped aqueous zinc-ion battery was obtained.

[0025] Preferably, the photoinitiator is one or more of 2-hydroxy-2-methylpropiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and 1-hydroxycyclohexylphenyl ketone;

[0026] The weak acid solution is a weak acid solution with a pH value of 2-3 obtained by dissolving an appropriate amount of acid in water and stirring for 1-5 hours; the acid is selected from one or more of citric acid, concentrated sulfuric acid, carbonic acid, hydrochloric acid, malic acid, oxalic acid or nitric acid.

[0027] Preferably, the photoinitiator uses UV light with a wavelength of 250-400nm, and the initiation time is 2-30min; the specifications of the conductive carbon filament are one or more of 1K, 3K, 12K, and 24K;

[0028] The diameter of the PTFE tubular mold is 0.5-3 mm;

[0029] The diameter of the heat shrink tube is 1-10mm.

[0030] Preferably, the constant voltage charging voltage in S3 is 1.6-2.4V, and the charging time is 1-120min.

[0031] A fiber-shaped electroluminescent device made using the bifunctional electrode fiber of the present invention is made by the following method:

[0032] Mix acrylamide, zinc sulfate heptahydrate and water, add NN methylenebisacrylamide, and mix to obtain an electroluminescent electrolyte; the electroluminescent electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 45-55% zinc sulfate heptahydrate, 0.05-0.5% NN methylenebisacrylamide, and the balance is water;

[0033] The thermal initiator and water are mixed to obtain a thermal initiator solution with a mass percentage of 5-10%; the thermal initiator is one or both of potassium persulfate and ammonium persulfate;

[0034] Take two of the bifunctional electrode fibers, insert them into a heat shrink tube, quickly mix the electroluminescent electrolyte and the thermal initiator solution and fill the heat shrink tube to make the weight ratio of the electroluminescent electrolyte to the thermal initiator be 400:1-200:1, initiate gelation at room temperature, and obtain a fiber-shaped electroluminescent device.

[0035] An application of the bifunctional electrode fiber described in the present invention in the preparation of an electroluminescent device.

[0036] The method of the present invention has simple preparation steps. The nanofiber layer prepared by electrostatic spinning can not only act as a diaphragm in the battery field to inhibit side reactions, but also can be used as a light-emitting layer and a dielectric layer in the electroluminescence field, integrating the two functions on one electrode fiber. By changing the formula in the electrolyte, fibrous zinc ion batteries and fibrous electroluminescent devices can be easily prepared. At the same time, a third fiber can be introduced into the fiber zinc ion battery to give it electroluminescent ability.

[0037] The present invention uses zinc wire as a substrate, and prepares a nanofiber layer on the surface of the zinc wire by electrostatic spinning, thereby constructing a dual-functional electrode fiber. The added PDMS is hydrophobic, and the photoinitiator usually has a lipophilic group, so the configured electrolyte can wet the nanofiber layer to provide the ion transmission channel required by the zinc ion battery; and when an electroluminescent electrolyte is used, since a thermal initiator without a lipophilic group is used, the solution cannot wet the nanofiber layer. At this time, the nanofiber layer can act as a light-emitting layer and a dielectric layer in the electroluminescent device, and electroluminescence can be performed through the liquid response mechanism after connecting an alternating current; it is worth mentioning that It is worth noting that when the zinc sulfate concentration is sufficient, the precursor solution can be quickly initiated at room temperature after dripping the heated initiator solution, reducing the possibility of the nanofiber layer being wetting and optimizing the process of the fiber electroluminescent device; and adding a third bifunctional electrode fiber to the constructed zinc ion battery system will not only not affect the energy storage function, but the positive and negative fibers of the zinc ion battery can charge the other electrode of the electroluminescent device, realizing the application of three electrode fibers satisfying two functions in one device; the device prepared by this preparation method belongs to the field of one-dimensional structure semi-solid-state batteries and electroluminescence, making it promising for application in the field of flexible electronics.

[0038] Compared with the prior art, the present invention has the following characteristics:

[0039] 1. The present invention uses an electrostatic spinning method to prepare a nanofiber layer on the surface of a zinc wire, and adds an electroluminescent material to the spinning solution to construct a dual-functional electrode fiber;

[0040] 2. The present invention uses different electrolytes to achieve different functional applications of bifunctional electrode fibers by controlling the components in the solution; when the electrolyte is used for photoinitiation, the lipophilic molecules can wet the nanofiber layer, and the special structure of the nanofiber can provide an electrolyte transmission channel for the battery. At the same time, zinc copper sulfide can provide more zinc-philic sites, and the dynamic BO bond in PDMS can reduce the hydrogen evolution reaction and inhibit the growth of zinc dendrites. Therefore, the fiber zinc ion battery has more excellent electrochemical performance; when the electroluminescent electrolyte is used, it cannot wet the nanofiber layer. At this time, the device is similar to a capacitor structure, and the nanofiber layer acts as a light-emitting layer and a dielectric layer in the system, which can effectively meet the electroluminescent function;

[0041] 3. The present invention uses the current collector of the active material to directly assemble the battery, which can reduce the time required for preparing the active material paste, and at the same time can reduce the uneven coating of the active material on the yarn surface and the loss caused by scratches in subsequent operations, greatly accelerating the preparation speed and stability, and laying the foundation for subsequent large-scale preparation;

[0042] 4. The present invention adds zinc sulfate of sufficient concentration to the acrylamide solution, which can be initiated at room temperature under the premise of using a thermal initiator for initiation, and has the advantages of rapidity and low energy consumption;

[0043] 5. The present invention can impart energy storage and electroluminescence functions to the same device through three electrode fibers, realizing energy storage-application integration, and providing new ideas for the development of the field of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The brightness curves of electroluminescent devices of zinc copper sulfide with different masses in Example 2;

[0045] Figure 2 The EIS spectra of zinc ion batteries with different masses of zinc copper sulfide in Example 2;

[0046] Figure 3 The SEM images and mapping images of the bifunctional electrode fibers of Supplementary Example 1, wherein Figure a is a SEM image, Figures bf are mapping images, (b) Si element (c) B element (d) O element (e) Zn element (f) Cu element;

[0047] Figure 4 The infrared spectrum analysis diagram of Supplementary Example 1;

[0048] Figure 5 To supplement the contact angle test of Example 2, Figure a shows the contact angle between the electrolyte for zinc ion battery and the nanofiber membrane, and Figure b shows the contact angle between the electroluminescent electrolyte and the nanofiber membrane;

[0049] Figure 6 To supplement the actual pictures of different gels in Example 3, the left one is the electrolyte for zinc ion battery, and the right one is the electroluminescent electrolyte;

[0050] Figure 7 To supplement the polarization performance test of Example 4, Figures ac are Nyquist plots before and after the chronoamperometry test, and Figures df are chronoamperometry test curves, where Figures a and d are zinc-zinc symmetric batteries, Figures b and e are TPU / PAM-based control batteries, and Figures c and f are PAM-based control batteries;

[0051] Figure 8 To supplement the Arrhenius curve and EIS spectra at different temperatures of Example 4, Figure a is the Arrhenius curve, Figures b and d are EIS spectra at different temperatures, Figure b is a zinc-zinc symmetric battery, Figure c is a TPU / PAM-based control battery, and Figure d is a PAM-based control battery;

[0052] Fig. 9 The linear sweep voltammetric curve of Supplementary Example 4;

[0053] Fig.10 The Tafel curve for supplementary example 4;

[0054] Fig.11 To supplement the rate performance test of the zinc-zinc symmetric battery in Example 4;

[0055] Fig.12 To supplement the long cycle performance test of the zinc-zinc symmetric battery in Example 4;

[0056] Fig.13 To supplement the long cycle performance test of the fiber zinc-manganese full battery in Example 5;

[0057] Fig.14 This is a lighting picture of the fiber electroluminescent device of Example 6;

[0058] Fig.15 The graph showing the variation of the brightness of the fiber electroluminescent device with voltage and frequency in Supplementary Example 6;

[0059] Fig.16 This is a graph showing the variation of the luminous color of the fiber electroluminescent device of Supplementary Example 6 with frequency. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0061] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0062] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.

[0063] The UV lamp model is WFH-204B, and the wavelength is 254nm, 365nm.

[0064] The present invention uses zinc wire as the main body, adds traditional electroluminescent materials, namely zinc copper sulfide and PDMS, into the spinning solution, and performs electrostatic spinning to obtain bifunctional electrode fibers; when the bifunctional electrode fibers are used as the negative electrode, the conductive carbon wires are used as the positive electrode current collector and are inserted into a heat shrink tube in parallel, and the heat shrink tube is filled with a weak acid gel electrolyte to construct a fiber zinc ion battery, and the manganese ions in the electrolyte are oxidized and deposited on the surface of the positive electrode current collector through constant voltage charging or chronoamperometry to form a final device; when two bifunctional electrode fibers are used to be inserted into a heat shrink tube in parallel and filled with an electroluminescent gel electrolyte to construct a fiber electroluminescent device.

[0065] Among them, the construction of the nanofiber layer gives the electrode fiber dual functions. By controlling the formula of the electrolyte precursor solution, it is effectively controlled whether the nanofiber layer is wetted. When the nanofiber layer is wetted, it can provide an ion transmission channel. At the same time, the polymer body in the nanofiber and the added zinc copper sulfide, PDMS can further protect the zinc negative electrode, thereby constructing a fiber battery. When the nanofiber layer is not wetted, the nanofiber layer acts as a light-emitting layer and a dielectric layer, effectively constructing a fiber electroluminescent device. Since the two devices are in similar environments, it is entirely possible to introduce a third electrode fiber in the fiber-shaped zinc ion battery system and give it an electroluminescent function, combining the electroluminescent function with energy storage into one device, and using a zinc ion battery to power the electroluminescent device, providing a new idea for the inheritance of fiber-shaped flexible electronic devices.

[0066] Example 1 Investigation of zinc sulfate concentration in electroluminescent electrolyte

[0067] Preparation of electroluminescent electrolyte

[0068] Take several portions of 3g acrylamide, add 7.5g deionized water respectively, then add 2.8g, 4.2g, 5.6g, 7g, 8.4g, 9.8g, 11.2g, 12.6g, 14g zinc sulfate heptahydrate in sequence and place on a stirrer and stir at room temperature for 5min, then add 20μg NN methylenebisacrylamide and place on a stirrer and stir for 5min to obtain electroluminescent electrolytes with different zinc sulfate heptahydrate contents;

[0069] 0.5 g of potassium persulfate was added into 10 g of deionized water, and the mixture was placed on a stirrer and stirred at room temperature for 10 min to obtain a thermal initiator solution.

[0070] Several portions of 200 mg of electroluminescent electrolyte were taken, and 10 mg of thermal initiator was added successively to observe the initiation process. The initiation time of electroluminescent electrolytes with different zinc sulfate heptahydrate contents is shown in Table 1.

[0071] Table 1

[0072]

[0073] Normally, the use of thermal initiators requires an environment with a temperature higher than 80°C to initiate gelation. However, when the electrolyte is in a high zinc sulfate concentration system, it can be initiated at room temperature. As shown in Table 1, when the amount of zinc sulfate heptahydrate added is less than 5.6g, the electrolyte is completely uninitiated and cannot form a gel. As the mass of zinc sulfate heptahydrate increases, it can be initiated in less than two minutes at room temperature. When the mass of zinc sulfate heptahydrate exceeds 9.8g, the initiation time is basically maintained within thirty seconds for rapid initiation. The rapid initiation of gel helps to fix water molecules and prevent the nanofiber layer from being penetrated to meet the needs of the electroluminescent device. When the mass of zinc sulfate heptahydrate exceeds 14g, it is close to saturation and cannot be completely dissolved.

[0074] Taking the cost and the initiation effect into consideration, the optimal concentration to be used is 45-55%.

[0075] Example 2 Investigation of the amount of zinc copper sulfide in the spinning solution for electrostatic spinning

[0076] 1. Preparation of spinning solution for electrospinning

[0077] 2g, 3g, 4g, 5g, 6g, and 7g of zinc copper sulfide were added to 5g of thermoplastic polyurethane in sequence, and dissolved in 7.5g of N-N-dimethylformamide and 7.5g of tetrahydrofuran solvent, and magnetically stirred for 12h at room temperature, and then 2g of PDMS was weighed and added to the solution, and magnetically stirred for 1h at room temperature again to form a uniform spinning solution;

[0078] 2. Preparation of bifunctional electrode fibers

[0079] Using 0.5 mm zinc wire as the core wire, the spinning solution prepared in step (1) was used, and electrospinning was performed using an electrospinning device. The angle between the needle tip and the collector was 60°, the distance between the needle tip and the collector was 8 cm, and the syringe pump pushed the spinning solution at a speed of 1.2 mL / h. During the spinning process, 16 KV DC high voltage electricity was used, the funnel-shaped collector speed was 80 rpm, and the winding device speed was 0.06 m / min to prepare bifunctional electrode fibers with different zinc copper sulfide concentrations.

[0080] 3. Preparation of neutral electrolyte

[0081] 3 g acrylamide and 8.4 g zinc sulfate heptahydrate were added to 7.5 g deionized water in sequence, and the mixture was placed on a stirrer and stirred at room temperature for 5 min. Then, 20 μg NN methylenebisacrylamide and 20 μL 2-hydroxy-2-methylpropiophenone were added in sequence, and the mixture was placed on a stirrer and stirred for 5 min to obtain a neutral electrolyte.

[0082] 4. Preparation of electroluminescent electrolyte

[0083] 3 g of acrylamide and 8.4 g of zinc sulfate heptahydrate were added to 7.5 g of deionized water in sequence, placed on a stirrer and stirred at room temperature for 5 min, and then 20 μg of N-N methylenebisacrylamide was added and placed on a stirrer and stirred for 5 min to obtain an electroluminescent electrolyte;

[0084] 0.5 g of potassium persulfate was added into 10 g of deionized water, and the mixture was placed on a stirrer and stirred at room temperature for 10 min to obtain a thermal initiator solution.

[0085] 5. Yarn-shaped stainless steel symmetrical battery test group

[0086] Taking the bifunctional electrode fiber as the substrate, two 5 cm bifunctional electrode fibers were sequentially stuffed into a polytetrafluoroethylene tubular mold with a diameter of 0.8 mm, and a neutral electrolyte was injected into the mold using a syringe. The fibers were photoinduced for 2 min using a UV lamp with a wavelength of 254 nm. After being taken out, the two fibers were again stuffed into a heat shrink tube with a diameter of 2 mm in parallel, and a neutral electrolyte was injected into the heat shrink tube using a syringe. The fibers were photoinduced for 10 min using a UV lamp with a wavelength of 254 nm to obtain a yarn-shaped zinc-zinc symmetrical battery.

[0087] 6. Preparation of yarn-shaped electroluminescent devices

[0088] Take 20 cm of the bifunctional electrode fiber prepared in Example 1 and a 0.5 mm zinc wire and insert them in parallel into a 1 mm diameter heat shrink tube, take 1 g of electroluminescent electrolyte and 0.05 g of thermal initiator solution, stir quickly, and inject them into the tube through a syringe to initiate gelation at room temperature, so as to construct a yarn-like electroluminescent device.

[0089] Table 2 shows the activation energy of zinc ion batteries with different zinc copper sulfide contents in Example 2.

[0090] Table 2

[0091] Mass of zinc copper sulfide (g) 2 3 4 5 6 7 <![CDATA[Activation energy (kJmol -1 )]]> 7.968 8.015 8.023 8.034 8.044 8.058

[0092] The concentration of zinc copper sulfide is one of the determining factors for the brightness of electroluminescent devices. At the same time, zinc copper sulfide can provide more zinc-affinity sites in zinc ion batteries, accelerate the transfer of zinc ions, and thus increase the cycle life of zinc ion batteries. Figure 1 As shown in the figure, under the condition of 300V 3kHZ, the brightness of the electroluminescent device increases with the increase of the concentration of zinc copper sulfide. When the mass of zinc copper sulfide exceeds 5g, the brightness of the electroluminescent device basically does not remain unchanged. The EIS spectrum of the prepared stainless steel symmetrical battery test is shown in the attached figure. Figure 2 As shown in Table 2, the calculated activation energy can be seen that as the quality of zinc copper sulfide increases, the resistance and activation energy are further reduced, which shows that zinc copper sulfide helps to improve the zinc ion transport. Combined with the performance of electroluminescent devices and zinc ion batteries, the optimal zinc copper sulfide concentration is finally considered to be 18.5%.

[0093] Example 3 Preparation method of dual-functional electrode fiber

[0094] 1. Preparation of spinning solution for electrospinning

[0095] Weigh 5 g of thermoplastic polyurethane and 5 g of zinc copper sulfide powder, dissolve them in 7.5 g of N-N-dimethylformamide and 7.5 g of tetrahydrofuran solvent, and stir them magnetically at room temperature for 12 h. Then weigh 2 g of PDMS and add it to the solution, and stir them magnetically at room temperature for 1 h to form a uniform spinning solution.

[0096] 2. Preparation of bifunctional electrode fibers

[0097] Using 0.5 mm zinc wire as the core wire, the spinning solution prepared in step (1) was used to perform electrostatic spinning using an electrospinning device. The angle between the needle tip and the collector was 60°, the distance between the needle tip and the collector was 8 cm, and the syringe pump pushed the spinning solution at a speed of 1.2 mL / h. During the spinning process, 16 KV DC high voltage electricity was used, the funnel-shaped collector rotated at 80 rpm, and the winding device speed was 0.06 m / min to prepare bifunctional electrode fibers.

[0098] Supplementary Example 1 Analysis of the morphology of bifunctional electrode fibers

[0099] 1. Morphology analysis: The actual image of the bifunctional electrode fiber prepared in Example 1 under ultraviolet light is shown in the attached figure. It can be seen that zinc copper sulfide is evenly attached to the yarn surface; the SEM image and mapping image of the bifunctional electrode fiber are shown in the attached figure. Figure 3As described above, it can be seen that the nanofiber layer prepared by electrospinning has uniform and smooth size and structure, and the fibers as a whole present a uniformly arranged structure. The element distribution of Zn, Cu, Si, and B shows that zinc copper sulfide and PDMS are relatively evenly dispersed without a granular structure. The uniform distribution of zinc copper sulfide plays an important role in accelerating the subsequent migration of zinc ions and uniform luminescence, while the uniform distribution of PDMS plays an important role in stabilizing hydrophobicity and inhibiting side reactions.

[0100] 2. Infrared spectrum analysis: as attached Figure 4 As shown, 794cm -1 Si-C stretching vibration peak, 1014 cm -1 The stretching vibration peaks of Si-O are 1058cm-1 and 1225cm -1 They are the bending vibration and stretching vibration peaks of BO, 1411 cm -1 and 1531cm -1 They are the characteristic peaks of amide I and amide II, 1731 cm -1 is the carbonyl vibration peak, 2964cm -1 is the stretching vibration peak of -CH3, 3347cm -1 It is the NH stretching peak of the amide bond, which further illustrates the uniform distribution of PDMS.

[0101] Example 4 Preparation method of nanofiber membrane

[0102] 1. Preparation of spinning solution for electrospinning: same as in Example 1.

[0103] 2. Preparation of nanofiber membrane

[0104] The spinning solution prepared in step (1) was used for electrospinning. The distance between the needle tip and the collector was 8 cm. The syringe pump pushed the spinning solution at a speed of 1.5 mL / h. During the spinning process, a 9 KV DC high voltage point was used and the collector speed was 150 rpm to prepare a nanofiber membrane.

[0105] 3. Preparation of neutral electrolyte

[0106] 3 g acrylamide and 8.4 g zinc sulfate heptahydrate were added to 7.5 g deionized water in sequence, and the mixture was placed on a stirrer and stirred at room temperature for 5 min. Then, 20 μg NN methylenebisacrylamide and 20 μL 2-hydroxy-2-methylpropiophenone were added in sequence, and the mixture was placed on a stirrer and stirred for 5 min to obtain a neutral electrolyte.

[0107] 4. Preparation of electroluminescent electrolyte

[0108] 3 g of acrylamide and 8.4 g of zinc sulfate heptahydrate were added to 7.5 g of deionized water in sequence, placed on a stirrer and stirred at room temperature for 5 min, and then 20 μg of N-N methylenebisacrylamide was added and placed on a stirrer and stirred for 5 min to obtain an electroluminescent electrolyte;

[0109] 0.5 g of potassium persulfate was added into 10 g of deionized water, and the mixture was placed on a stirrer and stirred at room temperature for 10 min to obtain a thermal initiator solution.

[0110] Supplementary Example 2 Wetting Performance Test

[0111] Due to the difference in structure between electroluminescent devices and zinc ion batteries, in zinc ion battery systems, it is necessary to promote the transmission of zinc ions between electrodes, while in electroluminescent devices, the electrodes need to be relatively insulated to construct a capacitor structure. Therefore, controlling the wetting of the nanofiber layer by the electrolyte becomes the key to selectively construct different devices. The nanofiber membrane prepared in step (2) of Example 2 was used as a test sample, and the precursor solution of steps (3) and (4) was used as the liquid. The contact angle was measured using a video contact angle tensiometer. 5 μL of liquid was dropped on the surface of the fiber membrane. The water contact angle was as shown in the attached figure. Figure 5 As shown. Due to the hydrophobicity of PDMS, the prepared nanofiber membrane has a certain hydrophobicity, so the nanofiber membrane presents a large contact angle when using an electroluminescent electrolyte, which causes the nanofiber layer to isolate the ion transmission between the two electrodes to meet the requirements of the electroluminescent device; and because the 2-hydroxy-2-methylpropiophenone added to the neutral electrolyte is an amphoteric molecule, the neutral electrolyte can effectively wet the nanofiber membrane. At this time, the nanofiber layer can form a double network structure with the gel, which can increase the transmission speed of zinc ions to improve the performance of zinc ion batteries.

[0112] Supplementary Example 3 Gel Properties

[0113] 200 mg of the electroluminescent electrolyte of step (4) of Example 2 was mixed with 10 mg of the thermal initiator solution at room temperature. Within one minute of the mixing of the solutions, the solutions reacted rapidly and polymerized to form a gel. 200 μL of the neutral electrolyte of step (3) was photoinduced by a UV lamp with a wavelength of 254 nm for 10 minutes to form a gel. Figure 6 As shown, the electroluminescent electrolyte has a more transparent transparency than the electrolyte for zinc ion batteries.

[0114] Example 5 Preparation of yarn-shaped zinc-zinc symmetric battery

[0115] Preparation of control group electrode fiber Weigh 5g of thermoplastic polyurethane and dissolve it in 7.5g of N-N dimethylformamide and 7.5g of tetrahydrofuran solvent, and stir magnetically for 12h at room temperature to form a uniform control group spinning solution. Using 0.5mm zinc wire as the core wire, the prepared spinning solution is used, and electrostatic spinning is performed using an electrospinning device. The angle between the needle tip and the collector is 60°, the distance between the needle tip and the collector is 8cm, and the injection pump pushes the spinning solution at a speed of 1.2mL / h. During the spinning process, 16KV DC high voltage electricity, a funnel-shaped collector speed of 80rpm, and a winding device speed of 0.06m / min are used to prepare the control group electrode fiber. Compared with the bifunctional electrode fiber spinning solution described in the present invention, the control group spinning solution does not contain 5g of zinc copper sulfide and 2g of PDMS.

[0116] Preparation of neutral electrolyte: same as in Example 2.

[0117] The bifunctional electrode fibers prepared in Example 1 and the electrode fibers prepared in the control group were used to prepare yarn-shaped zinc-zinc symmetric batteries.

[0118] 1. Yarn-shaped zinc-zinc symmetric battery test group

[0119] Taking the bifunctional electrode fiber as the substrate, two 5 cm bifunctional electrode fibers were sequentially stuffed into a polytetrafluoroethylene tubular mold with a diameter of 0.8 mm, and a neutral electrolyte was injected into the mold using a syringe. The fibers were photoinduced for 2 min using a UV lamp with a wavelength of 254 nm. After being taken out, the two fibers were again stuffed into a heat shrink tube with a diameter of 2 mm in parallel, and a neutral electrolyte was injected into the heat shrink tube using a syringe. The fibers were photoinduced for 10 min using a UV lamp with a wavelength of 254 nm to obtain a yarn-shaped zinc-zinc symmetrical battery.

[0120] 2. Yarn-shaped zinc-zinc symmetric battery control group

[0121] The yarn-like Zn-symmetric TPU / PAM-based control battery was prepared in the same way, except that the control group electrode fibers were used as the substrate, and two 5-cm control group electrode fibers were taken and stuffed into the polytetrafluoroethylene tubular mold in sequence.

[0122] The yarn-like Zn-Zn symmetric PAM-based control cells were prepared in the same way, except that 0.5 mm zinc wire was used as the substrate, and two 5 cm zinc wires were taken and stuffed into a polytetrafluoroethylene tubular mold in sequence.

[0123] Supplementary Example 4 Testing of zinc protection performance of yarn-shaped zinc-zinc symmetric battery

[0124] 1. Polarization test: The prepared zinc-zinc symmetrical battery was used for testing. The EIS spectrum of 10m-100K was first tested by the electrochemical workstation. The chronoamperometry was used for the planned test for 2h at a constant polarization potential of 10mV. The polarized symmetrical battery was tested again for the EIS spectrum of 10m-100K. The prepared PAM-based control battery and TPU / PAM-based control battery were used as the control group. The test results are shown in the attached figure. Figure 7 As shown in the figure, the zinc ion migration number (t Zn 2+ ) is 0.732, while the TPU / PAM-based control battery and the PAM-based control battery are only 0.603 and 0.463, respectively. Zn 2+ The value will lead to the Zn 2+ Ion concentration polarization exacerbates the problem of zinc dendrites and parasitic side reactions, t Zn 2+ The improvement is due to the fact that copper zinc sulfide can provide more zinc-philic sites and accelerate the transfer of zinc ions, thus achieving stable and continuous 3D spatial zinc accumulation on the zinc metal surface.

[0125] 2. Arrhenius curve: The prepared zinc-zinc symmetric battery was used for testing. The EIS spectrum of 10m-100K was tested on an electrochemical workstation at 30-80°C, and the Arrhenius curve was prepared by fitting. The prepared PAM-based control battery and TPU / PAM-based control battery were used as control groups, as shown in the attached figure. Figure 8 As shown in Figure 2, according to the Arrhenius equation, the activation energy (Ea) values ​​of the yarn-shaped Zn-Zn symmetric battery, the TPU / PAM-based control battery, and the PAM-based control battery are 10.98, 20.03, and 23.86 kJ mol, respectively. -1 The lowest Ea of the yarn-shaped Zn-Zn symmetric cell indicates that the doping of Zn-CuS and the nanofiber layer of PDMS are beneficial to the Zn 2+ The desolvation process has a positive effect on the deposition / dissolution kinetics of Zn on the anode surface. This is also due to the strong interaction between ZnS and Zn ions, which significantly reduces the dissolution energy barrier, prevents water from entering the solvation sheath, and promotes the deposition / dissolution kinetics of Zn on the anode surface. 2+ Dissolves faster with less energy expenditure.

[0126] 3. Linear sweep voltammetry curve and Tafel curve: The prepared Zn-Zn symmetric battery was used for testing. The electrochemical workstation was used to measure the linear sweep voltammetry curve at 0.1 mV s -1 Linear sweep voltammetry was performed, and the prepared PAM-based control battery and TPU / PAM-based control battery were used as the control group. Fig. 9As shown in the figure, after negative scanning, the current of the Zn-Zn symmetric battery is less than that of the PAM-based control battery and the TPU / PAM-based control battery, which indicates that the kinetics of hydrogen evolution at the Zn-PTP interface is suppressed, and the hydrogen evolution voltage between -0.14 and -0.03 is significantly reduced, and a lower slope is shown during the current increase, which indicates that the zinc anode provides excellent inhibition of hydrogen absorption reaction and corrosion reaction; Tafel curve is shown in the attached figure. Fig.10 As shown in Figure 2, the corrosion voltage of the yarn-shaped Zn-Zn symmetric cell is -0.010 V and the corrosion current is 3.247 mA cm -2 , which is much lower than the TPU / PAM-based control battery (-0.021V / 8.144mAcm -2 ) and PAM-based control cells (-0.028V / 10.56mAcm -2 ), indicating a slow corrosion rate, which is due to the dynamic BO bonds in PDMS that can effectively lighten the hydrogen evolution reaction and inhibit the growth of zinc dendrites;

[0127] 4. Rate performance test: The prepared zinc-zinc symmetrical battery was used for testing, and the rate performance was tested at 1-8 mA cm -2 The current density is 1 mAh cm -2 The capacity of the prepared PAM-based control battery and the TPU / PAM-based control battery were used as the control group. Fig.11 As shown in the figure, it can be seen that when the current density is increased from 1mAcm -2 Up to 10mAcm -2 When the current density returns to 1 mA cm -2 , the battery overpotential can also return to 0.1V. In contrast, the TPU / PAM-based control battery has a high current density of 10mA cm -2 In the case of , the battery overpotential increased to 0.3V, while the PAM-based control battery reached a current density of 5mAcm -2 A short circuit occurred when the Zn / Zn symmetric battery was charged, which shows that the Zn / Zn symmetric battery has excellent rate performance.

[0128] 5. Long cycle performance test: The prepared zinc-zinc symmetrical battery was used for testing. The battery was tested at 1 mA cm -2 The current density is 1 mAh cm -2 The capacity of the long cycle performance test, as shown in the attached Fig.12 As shown, the battery operated normally for more than 400 hours, and the voltage hysteresis after 400 hours of operation only slightly increased to 120mV, indicating its ultra-long life.

[0129] Example 6 Preparation of Yarn-like Aqueous Zinc Ion Battery

[0130] Neutral electrolyte: same as in Example 2;

[0131] Weakly acidic electrolyte: 3 g acrylamide, 8.4 g zinc sulfate heptahydrate, 1.7 g manganese sulfate monohydrate, and 0.05 g citric acid were added to 7.2 g deionized water in sequence, placed on a stirrer and stirred at room temperature for 5 min, then 20 μg NN methylenebisacrylamide and 20 μL 2-hydroxy-2-methylpropiophenone were added in sequence and placed on a stirrer and stirred for 5 min to obtain a weakly acidic electrolyte.

[0132] Preparation of yarn-shaped aqueous zinc ion battery: 5 cm of the bifunctional electrode fiber prepared in Example 1 was stuffed into a polytetrafluoroethylene tubular mold with a diameter of 0.8 mm, a neutral electrolyte was injected into the mold using a syringe, and photoinitiated for 2 minutes by a UV lamp with a wavelength of 254 nm. After taking it out, it was stuffed into a heat shrink tube with a diameter of 2 mm in parallel with a 5 cm long 3K conductive carbon filament, a weak acid electrolyte was injected into the heat shrink tube using a syringe, and photoinitiated for 10 minutes by a UV lamp with a wavelength of 254 nm to obtain a yarn-shaped zinc ion battery.

[0133] Supplementary Example 5 Electrochemical Performance Test of Yarn-like Aqueous Zinc Ion Battery

[0134] Long cycle test: The battery was charged at 2.2V constant voltage for 5 min and at 0.5mAcm -2 The current density is constant current discharge, as shown in the attached Fig.13 As shown, the battery cycle number can reach more than 700 cycles, indicating its good cycle life. The battery capacity gradually increases in the first 100 cycles, and the capacity remains basically stable after 100 cycles. After 700 cycles, the capacity retention rate can still be maintained at 100%. At the same time, the efficiency is basically maintained at 95%-100%, indicating that the battery has good charge and discharge capabilities.

[0135] Example 7 Preparation of yarn-shaped electroluminescent device

[0136] Preparation of electroluminescent electrolyte: same as in Example 2;

[0137] Take 20 cm of the bifunctional electrode fiber prepared in Example 1 and a 0.5 mm zinc wire and insert them in parallel into a 1 mm diameter heat shrink tube, take 1 g of electroluminescent electrolyte and 0.05 g of thermal initiator solution, stir quickly, and inject them into the tube through a syringe to initiate gelation at room temperature, so as to construct a yarn-like electroluminescent device.

[0138] By connecting the electrodes at both ends of the yarn-shaped electroluminescent device through an EL driver, the device can be lit up, as shown in the attached Fig.14As shown, since the luminescent powder is evenly dispersed, the prepared yarn-shaped electroluminescent device emits light evenly. At the same time, due to the insulating properties of PDMS, the wetting of the nanofiber layer is effectively prevented. When the precursor solution is triggered, most of the water molecules are fixed by the gel to become bound water, and the probability of the nanofiber layer being wetting is further reduced, which allows the device to emit light stably for a long time.

[0139] Supplementary Example 6: Test of Luminescence Performance of Yarn-Shaped Electroluminescent Device

[0140] The electroluminescent device prepared in Example 5 was tested. Fig.15 As shown in the figure, as the load voltage increases, the brightness of the yarn-shaped electroluminescent device increases accordingly. In addition, since the frequency has a positive effect on the generation of electron holes and the excitation of the luminescent center, the brightness will be further improved when the frequency increases from 1 kHz to 6 kHz. At the same time, the frequency will also cause the change of the electroluminescent color, as shown in the figure. Fig.16 As shown, with the increase of frequency, the electroluminescence color can obviously change from green to blue, which provides a possibility for the preparation of tunable light-emitting fibers.

[0141] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0142] The above is a detailed introduction to an electroluminescent bifunctional electrode fiber provided by the present invention and its application in the preparation of an electroluminescent device. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A dual-functional electrode fiber, Features The bifunctional electrode fiber is prepared by the following method: A zinc wire with a diameter of 0.3-2.0 mm is used as a core wire, and a spinning solution is used to electrospin the surface of the zinc wire to form a nanofiber layer, thereby preparing a dual-functional electrode fiber; The spinning solution contains 15-25% of thermoplastic polyurethane, 5-20% of zinc copper sulfide, 2-10% of PDMS, and the balance is a solvent composed of NN dimethylformamide and tetrahydrofuran, the mass ratio of NN dimethylformamide to tetrahydrofuran in the solvent is 100:0-50:50, and the molecular weight of the thermoplastic polyurethane is 10000-50000. The fibers attached to the zinc wire surface are controlled by adjusting the winding device speed, the funnel collector rotation speed, the injector flow rate and the positive and negative voltages.

2. The bifunctional electrode fiber according to claim 1, Features: The electrospinning parameters were set as follows: the angle between the needle tip and the collector was 60°, the distance between the needle tip and the collector was 8 cm, the syringe pump pushed the spinning solution at a speed of 1.2 mL / h, 12-17 KV DC high voltage electricity was used during the spinning process, the funnel-shaped collector rotated at a speed of 120-240 rpm, and the winding device speed was 0.06 m / min.

3. The bifunctional electrode fiber according to claim 1, Features: The spinning solution contains 18-20% of thermoplastic polyurethane, 18-20% of zinc copper sulfide, 7-8% of PDMS, and the balance is a solvent composed of NN dimethylformamide and tetrahydrofuran, wherein the mass ratio of NN dimethylformamide to tetrahydrofuran in the solvent is 50:

50.

4. A fibrous aqueous zinc ion battery made using the bifunctional electrode fiber according to claim 1, Features The fiber-shaped zinc ion battery is prepared by the following method: S1 Preparation of electrolyte Adding acrylamide and zinc sulfate heptahydrate to water in sequence and mixing them evenly, then adding NN methylenebisacrylamide and a photoinitiator in sequence and mixing them evenly to obtain a neutral electrolyte; the neutral electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 45-55% zinc sulfate heptahydrate, 0.05-0.5% NN methylenebisacrylamide, 0.05-0.5% photoinitiator, and the balance is water; Add acrylamide, zinc sulfate heptahydrate and manganese sulfate to a weak acid solution with a pH value of 2-3 and mix well, then add NN methylenebisacrylamide and a photoinitiator in sequence, and mix well to obtain a weak acid electrolyte; the weak acid electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 40-50% zinc sulfate heptahydrate, 5-10% manganese sulfate, 0.05-0.5% NN methylenebisacrylamide, 0.05-0.5% photoinitiator, and the balance is a weak acid solution, and the pH value of the solution is 3-5; Preparation of S2 fiber-shaped aqueous zinc-ion batteries The bifunctional electrode fiber is used as the negative electrode and inserted into a polytetrafluoroethylene tubular mold, and the neutral electrolyte prepared by S1 is injected into the mold for photoinitiation to obtain a bifunctional electrode fiber / photoinitiator gel electrolyte yarn; The bifunctional electrode fiber and the conductive carbon filament are used as positive electrode current collectors, two bifunctional electrode fiber / photoinitiator gel electrolyte yarns are inserted into a heat shrink tube in parallel, and the weak acid electrolyte prepared by S1 is injected into the heat shrink tube using a syringe, and light initiation is performed to obtain a yarn-shaped aqueous zinc ion battery without a positive electrode; S3 Active Material Loading The positive electrode-free yarn-shaped aqueous zinc-ion battery prepared with S2 was used as a device. The manganese ions in the electrolyte were oxidized into manganese oxides and deposited on the surface of the positive electrode current collector by chronoamperometry or constant voltage charging for several minutes under constant voltage conditions using an electrochemical workstation or a blue electric workstation. The yarn-shaped aqueous zinc-ion battery was obtained.

5. The fibrous aqueous zinc ion battery according to claim 4, Features: The photoinitiator is one or more of 2-hydroxy-2-methylpropiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and 1-hydroxycyclohexylphenyl ketone; The weak acid solution is a weak acid solution with a pH value of 2-3 obtained by dissolving an appropriate amount of acid in water and stirring for 1-5 hours; the acid is selected from one or more of citric acid, concentrated sulfuric acid, carbonic acid, hydrochloric acid, malic acid, oxalic acid or nitric acid.

6. The fibrous aqueous zinc ion battery according to claim 4, Features: Photoinitiation uses UV light with a wavelength of 250-400nm, and the initiation time is 2-30min; The specifications of the conductive carbon filament are one or more of 1K, 3K, 12K and 24K; The diameter of the PTFE tubular mold is 0.5-3 mm; The diameter of the heat shrink tube is 1-10mm.

7. The fibrous aqueous zinc ion battery according to claim 4, Features: The constant voltage charging voltage in S3 is 1.6-2.4V, and the charging time is 1-120min.

8. A fiber-shaped electroluminescent device made using the bifunctional electrode fiber according to claim 1, Features The fiber-shaped electroluminescent device is prepared by the following method: Mix acrylamide, zinc sulfate heptahydrate and water, add NN methylenebisacrylamide, and mix to obtain an electroluminescent electrolyte; the electroluminescent electrolyte contains the following components in percentage by mass: 10-20% acrylamide, 45-55% zinc sulfate heptahydrate, 0.05-0.5% NN methylenebisacrylamide, and the balance is water; Mix the thermal initiator and water to obtain a thermal initiator solution with a mass percentage of 5-10%; The thermal initiator is one or both of potassium persulfate and ammonium persulfate; Take two of the bifunctional electrode fibers, insert them into a heat shrink tube, quickly mix the electroluminescent electrolyte and the thermal initiator solution and fill the heat shrink tube to make the weight ratio of the electroluminescent electrolyte to the thermal initiator be 400:1-200:1, initiate gelation at room temperature, and obtain a fiber-shaped electroluminescent device.

9. Use of the bifunctional electrode fiber according to claim 1 in preparing an electroluminescent device.

Citation Information

Patent Citations

  • Elastoluminescence composite material as well as preparation method and application thereof

    CN111978949A

  • Information encryption dynamic display system and manufacturing method thereof

    CN115169514A

  • Preparation method of multi-axis flexible light-emitting fiber capable of emitting light through stretching and pressing

    CN115726193A

  • Preparation method of PDMS / ZnS: Cu composite material

    CN116554688A

  • Yarn-shaped aqueous zinc-manganese battery and preparation method thereof

    CN117543103A